Comparison of complications in diabetic outpatients with or without mental illness - Robin Maskey; Dhana Ratna Shakya; Sanjib Kumar Sharma; Prahlad Karki; Poonam Lavaju; Jouslin Kishore Baranwal (Indian Journal of Endocrinology and Metabolism, 2013)
Diabetes Mellitus (DM) and psychiatric illness are related in many ways by prevalence, burden, course, and outcome. Co-morbid mental illness may play a role in determining the complication in diabetic patients. This study was conducted in 2010 among consecutive diabetic out-patients diagnosed as per American Diabetes Association (ADA) guidelines 2009, of age above 14 years, to compare the complications in diabetic patients with or without mental illness. Diabetic neuropathies, cardiovascular complications, and morbid obesity were among the complications significantly more among diabetic patients with mental illness (GHQ-12 ≥ 2) than without mental illness (GHQ-12 ≤ 2).